Epidemiological Surveillance over Community-Acquired Pneumonia as One of the Means for Biological Safety Provision - G. G. Onishchenko; E. B. Ezhlova; Yu. V. Demina (Проблемы особо опасных инфекций, 2013)
Community-acquired pneumonia (CAP) ranges among the most widely spread emerging infectious diseases both in the Russian Federation and around the world. It is one of the main factors contributing to morbidity and mortality among the population. Adult cohort suffers from community-acquired pneumonia to the highest degree. Lethal cases are often registered in the active working age. According to the statistics morbidity rate for CAP in Russia reaches 14–15 %, while actual value is significantly higher, than the one under record. Total number is approximately 1,5 million cases per year. Base number of infections is accounted for bacterial pneumonia. However considerable part of it is caused by other microorganisms, including viruses. Up-to-date community-acquired pneumonia is of a great epidemiological and clinical value, and development of epidemiological surveillance system is an urging issue, that might allow for elaboration of the methodology for carrying out proper monitoring and preventive measures.